Role of Vitamins and Nutrition in Old Age as Immune Modulator with Future Prospective - Tahani Nasser Almofeed Altamimi; Fahmida Khatoon Zahid Balouch; Ruba Mustafa Elsaid Ahmed (Research Highlights in Disease and Health Research Vol. 4, 2023)
Old age is best defined as age of retirement that is 60 years and above. Nutrition for old age is known as Geriatric Nutrition. Aging brings physiological, psychological and immunological changes which influence the nutritional status. Use of health food and Anti oxidant like Vitamin D, C and E can help the body immune response against Virus.Present Dementia and CVD may share risk factors like high intake of dietary total fat. Emphasis should be placed on reducing the intake of saturated fat and choosing mono saturated or poly saturated fat sources. Sufficient intake of ?-3 fatty acids helps in visual acuity, hair loss, tissue inflammation, improper digestion, poor kidney function and mental depression. Study discuss the role of these vitamin to for Host immune against aging. Due to decrease appetite and poor digestion, old people consume less protein which may lead to edema, anemia, and low resistance to infections. According to data from acute hospitalization studies of older persons, up to 71% are nutritionally vulnerable or malnourished, that’s increased their mortality risk.